Pengaruh Modal Usaha, Tenaga Kerja dan Lama Usaha terhadap Pendapatan Sentra Tahu di Desa Ledok Kulon Kecamatan Bojonegoro - Etha Lorenza Grendwipradita; Muhammad Yasin (Studi Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: The purpose of this study is that there is an influence of business capital, labor, and length of business on the income of the tofu center business in Ledok Kulon Village, Bojonegoro Regency. Methodology: This study uses quantitative methods with data collection techniques of questionnaires, interviews, and documentation. The method used is multiple linear regression analysis, determination analysis (R2), and hypothesis testing. This data collection technique was carried out by distributing questionnaires to 38 respondents, namely the Tofu Industry in Ledok Kulon Village, Bojonegoro Regency. Result: The results of this study indicate that it is partially significant, namely (1) business capital (X1) has a positive and significant effect on Tofu Sentra income which shows a Tcount value of 13.084 with a significance value of 0.000 and (2) Length of Business (X3) has a positive and significant effect on income the tofu center shows a Tcount value of 2.298 with a significant value of 0.28 while the variable (3) Labor (X2) has a positive but not significant effect on the income of the tofu business center which shows a Tcount value of 1.096 and a significance value of 0.281. Analysis of the coefficient of determination shows a value of 0.940 which means that the independent variables of company capital, labor and length of business have an influence of 94.0% on the income of the dependent variable, and the remainder reaches 6%. explained by other variables outside the research model of the audit fee, relevant information can be obtained.